Estimating the benefits and costs of forming business partnerships - LEE, Jungho (Institutional Knowledge at Singapore Management University, 2020)
I estimate a matching model of business‐partnership formation to quantify the relative importance of productivity gains, financing gains, and the coordination failure of effort provision (moral hazard) among partners. Productivity gains account for 61% of the gain from the observed partnerships. For partners in the first quartile of the wealth distribution, however, financing accounts for 93% of the gain. The cost of moral hazard corresponds to 42% of the entire gain from partnerships. A loan policy specifically targeting partnerships is less effective in improving welfare than a conventional loan policy that provides loans to individual entrepreneurs.